(untitled) (Fiep Bulletin - online, 2015)
The Elders National Politics grants that every aged has the right of his own autonomy, integration and effective participation on the society. The loss of autonomy is generally associated to the reduction or loss of efficiency of some organs and systems, affecting the functional capacity. The objective of this study was to analyze the aspects of the functional capacity of the aged living at the Life Village Condominium in Jataí GO. The studied group was of 41 aged 19 women and 22 men with ages between 54 and 93 years. In order to collect the data we used a form with Daily Life Activities (DLAs) and Instrumental Daily Life Activities (IDLAs). Through this study we could conclude that the studied group has greater difficulties in the IDLAs than in the DLAs. Dividing the results into genders there was no great difference in the results in the DLAs the same not occurring in the IDLAs, because in these activities there’s a greater number of independent men compared to the women. Starting from the analyzed results of our studies we’ll be able to contribute so that more data related to the functional capacity of the aged is obtained, raising the chances that more trustful parameters about this subject are established.